Eco-Cycle: Organic Waste Processing and Sustainable Energy Development through Collaborative Institutional Engagement - Setyawati Yani; Rismawati Rasyid; Thahirah Arief; Astuti, Andi Rina Ayu; Muhammad Budi Adiputra Reski; Omar Hassouna (Candela Edutech Indonesia, 2025)
Educational institutions generate substantial organic waste, contributing to environmental challenges such as overflowing landfills and methane emissions. Globally, food waste alone accounts for an estimated 8-10% of greenhouse gas emissions, and in Malaysia, nearly 45% of municipal solid waste is organic material. To address these issues, an international community engagement project was implemented as a collaboration between Universitas Muslim Indonesia (UMI) and a higher education institution in Malaysia. The project aimed to develop a sustainable campus waste-management model by converting organic waste into valuable resources (biogas for energy and compost for agriculture) while fostering cross-border academic cooperation. Due to logistical constraints, the program was conducted via virtual platforms, involving webinars, workshops, and digital campaigns that engaged over 60 participants (students, faculty, and staff) from both institutions. The project combined technical planning—such as proposing an anaerobic digestion system for biogas production—with a virtual community outreach approach to educate and involve stakeholders in organic waste management best practices. It serves as a replicable model for other institutions seeking to integrate community engagement with sustainability initiatives. The international collaboration not only advanced knowledge and awareness of organic waste management but also strengthened bilateral ties, demonstrating how virtual engagement can overcome geographical barriers to promote global sustainability goals. The outcomes suggest that with further support, this initiative can evolve into a fully operational waste-to-energy program, exemplifying how universities can act as living laboratories for circular economy practices.